Experiential Learning in Tourism in Cambodia: Roles of Service Quality in Enhancing Customer Satisfaction and Behavioral Intention in the Digital Era - Sovantha Ros; Sarom Mok (Universitas Majalengka, 2026)
In this study, tourism service quality is considered an experiential learning process to increase customer satisfaction and behavioral intention in the digital era. These aspects can be studied in the context of tourism in Siem Reap, Cambodia, by examining the relationship between tourism service quality, customer satisfaction, behavioral intention, and the moderating effect of experiential learning. A quantitative research design was carried out using a structured questionnaire with 400 international tourists. Structural Equation Modeling (SEM) was applied to the relationship between the variables, and mediating and moderating effects were analyzed. We found that tourism service quality positively impacts customer satisfaction (β = 0.62, p < 0.001), while customer satisfaction has a significant effect on behavioral intention (β = 0.68, p < 0.001). The mediation analysis explains that customer satisfaction significantly mediates the relationship of tourism service quality and behavioral intention (β = 0.42, p < 0.001). Experiential learning also moderates the relationship between tourism service quality and customer satisfaction (β = 0.21, p < 0.05) and customer satisfaction and behavioral intention (β = 0.19, p < 0.05). The model demonstrates a beneficial fit with the data. These findings indicate the need to integrate service quality and experiential learning to enhance customer satisfaction and behavioral intention. The research of this study is both tourism and educational in nature, as tourism is considered an experiential learning process and thus is useful for the development of sustainable and engaging tourism in the digital era.